Sabun Cuci Tangan Cair dari Limbah Daun Galam (Melaleuca Cajuputi) - Muh Azhari; Rudy Yoga Lesmana (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
This activity aims to reduce the biomass of Galam leaf waste and provide opportunities to process waste leaves into a business for the people of Palangkaraya City. The method used is the demonstration method of making the product. Liquid hand washing soap from Galam Leaf Waste can be a solution to overcome environmental problems and open up opportunities to process waste leaves into a business.